Dayak and Their Daily Life - Hamid Darmadi (JETL (Journal of Education, Teaching and Learning), 2017)
This article titled "Dayak and Daily Life" This paper aims to reveal the Dayak and in their daily life. Dayak is a native of Borneo has its own characteristics. Dayak, divided into 405 sub-sub clans [1]. Each sub Dayak both Indonesia and Malaysia are identical. Dayak customs and culture comes from the word "Power" which means upstream, to refer to people who live in inland areas or in the interior of Borneo. In the arsenal of art and culture, Dayak has many similarities such as; saber, chopsticks, beliong, betang, cupai, renjung, empajang and others. Dayak indigenous religion is Kaharingan which is the original religion born of the cultural ancestors of the Dayaks. Most of the Dayak people still adhere to the belief of the existence of unseen objects in certain places such as rocks, large trees, planting gardens in the forest, lakes, pools, and others are believed to have "magical powers". Daily life of the Dayaks in general farming, farming. When will open farming land, farming they held ritual.